Important modifications in dielectric properties of LDPE after contact with some foods - Sameh M. Elghnam; Youssef H. Abdelalim; Mahmoud A. Hamad (Journal of Taibah University for Science, 2022)
We analyzed the dielectric properties of low density polyethylene (LDPE) grad (LA071) materials after different time intervals of contact with apple, pineapple, mango, and cow’s milk. Cole–Cole plots show the distribution of relaxation, depending on the time of contact and the type of food. Furthermore, chemical processes between LDPE and foods lead to significant changes in the dielectric properties of LDPE samples, relying on contact time and food type. In our study, contact with cow’s milk causes the most LDPE degradation, whereas contact with mango causes the least LDPE degradation. It is suggested that dielectric measurements be used as indicators of LDPE degradation and some other defects.